O papel docente na educação infantil: impactos da formação contínua no repensar profissional de professoras que trabalham com crianças menores de seis anos. - Silva, Thaís Coutinho de Souza (2021)
The research presents discussions about continuing teacher education, with teachers who work in the context of early childhood education and assist children under six years old, based on the assumptions of collaborative action research and the theoretical framework of historical-critical pedagogy for education based on scientific knowledge. The theme`s problematization was based on three fundamental questions: how does continuous education allow reflections on the main training needs related to the professional performance of early childhood education`s teachers, collaborators in research? Were there changes in the teachers' conceptions about the role of early childhood education from the formative meetings? How did continuing education impact the rethinking of teachers' professional performance, based on their own assessments? In this context, the main purpose of the study was conducted a proposal for continuous education, with a view to identifying, analyzing and overcoming the training needs unveiled by the collaborators, and rethinking the role of early childhood education for the integral education of the child, in addition to understanding the impacts of training meetings for the professional performance of teachers and possible repercussions. The investigated scenario is a municipal child education school in Uberlândia that serves children from zero to four years of age. The data were produced from fortnightly formative meetings with a collaborative group composed of seven teachers, in a total of eight meetings lasting approximately three hours each. We conducted questionnaires, debates, motivating questions, representative badges, the production of a teaching letter and the making of a memory device to create the research corpus. Based on the manifested training needs, we categorized and developed the proposal for continuous education addressing three themes: 1) the relationship between theory and practice in initial and continuous education; 2) professional devaluation in early childhood education; 3) assumptions of pedagogical theories and learning theories. The research results showed that the unity between academic research and pedagogical practice in fact became constituents and constituents of meaning in the process of continuous education of the collaborators. The use of the theoretical framework of historical-critical pedagogy as a basis for reflecting on professional performance, brought valuable contributions to anchor the possibilities of intervening in the school reality. We defend the need for continuous education to significantly advance beyond the reflection of practice on practice, offering teachers access to scientific knowledge within their work context. As a consequence of the investigation, we present two main ideas: the “theoretical repulsion” and the “formation by scientific knowledge”.